2017
DOI: 10.1055/s-0037-1604048
|View full text |Cite
|
Sign up to set email alerts
|

Stentless Bioprostheses for Aortic Valve Replacement in Octogenarians: The Influence of Coronary Artery Disease

Abstract: Use of the Freestyle stentless valve prosthesis for AVR is feasible also in octogenarians. The existence of coronary artery disease leads to concomitant bypass surgery, but not a higher level of perioperative or long-term mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Across the included studies, the reported mean follow-up ranged between 2.4 [ 16 ] and 6.6 years [ 18 ] with a weighted mean follow-up of 5.1 years. The longest follow-up was 15 years [ 22 ]. All included studies reported at least 5-year follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across the included studies, the reported mean follow-up ranged between 2.4 [ 16 ] and 6.6 years [ 18 ] with a weighted mean follow-up of 5.1 years. The longest follow-up was 15 years [ 22 ]. All included studies reported at least 5-year follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies presented data on postoperative CVE [ 3 , 4 , 15–17 , 19 , 20 , 22 , 23 ]. There was no difference between the 2 groups (OR = 0.92; 95% CI = 0.61–1.39; P = 0.69) and no heterogeneity was revealed across the studies ( I 2 = 0%; Supplementary Material, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3B). When we restricted the analysis for those studies ( n = 12) [ 7 , 9 , 10 , 13 , 19 , 20 , 38 , 39 , 41 , 45 , 51 , 52 ] reporting a maximum follow-up of 10 years or more, the pooled analysis revealed no differences between the two groups (HR = 0.97; 95% CI 0.87–1.09; p = 0.64) with evidence of moderate heterogeneity ( I 2 = 44%; Tau 2 = 0.01; p = 0.05) (Fig. 2 B) and with no evidence of publication bias (Egger’s linear regression test: p = 0.83; Begg and Mazumdar’s test: p = 0.90) (Supplemental material, Fig.…”
Section: Resultsmentioning
confidence: 99%